2019
DOI: 10.1136/neurintsurg-2019-014920
|View full text |Cite
|
Sign up to set email alerts
|

Maturing institutional experience with the transradial approach for diagnostic cerebral arteriography: overcoming the learning curve

Abstract: BackgroundDespite growing interest in the transradial approach for neurovascular procedures, prospective data about the learning curve for neurointerventionalists adopting this approach are limited.MethodsA subsequent prospective series of 50 consecutive right transradial diagnostic cerebral arteriograms was compared with our initial institutional experience using a procedural staging system. The primary outcome was the ability to achieve the predefined procedural goals using the radial approach. Secondary out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
31
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 9 publications
4
31
0
1
Order By: Relevance
“…However, given the indisputable advantages of wrist access, some neurovascular centers have recently accepted the challenge and switched their approach to a transradial access for diagnostic and interventional procedures with great success 1–6…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, given the indisputable advantages of wrist access, some neurovascular centers have recently accepted the challenge and switched their approach to a transradial access for diagnostic and interventional procedures with great success 1–6…”
Section: Discussionmentioning
confidence: 99%
“…The neurointerventional field has recently adopted the transradial approach for diagnostic angiographies and interventional procedures 1–6. Faster postprocedural recovery, higher patient satisfaction, and fewer access site complications are some of the major advantages of wrist access over the transfemoral approach.…”
Section: Introductionmentioning
confidence: 99%
“…However, TRA comes with a significant learning curve similar to any new surgical technique. A study of 942 new radial operators for percutaneous coronary intervention found a threshold of 30–50 cases at which time improvements in procedural metrics began to flatten 13 14. Our center has undergone an extensive exploration into transitioning our practice from TFA to TRA for the majority of our procedures 15–19.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the clear benefit of transradial access in the interventional cardiology literature,14 15 at present the vast majority of cerebral angiography is still performed via the transfemoral approach. However, transradial access for cerebral angiography and neurointervention has gained popularity over the past few years,16–18 and early evidence suggests the same benefits that have been studied in cardiology can be applied to the neuroangiographic procedures 19–22. As an extension of the trend towards radial access in cerebral angiography, many of the benefits of transradial access can be extrapolated to IOA.…”
Section: Introductionmentioning
confidence: 99%